Pola Komunikasi Antarpribadi Guru Dan Siswa Tunarungu Di Slb Taman Pendidikan Islam Kota Medan - Zendha Jepani Anjerini; Indira Fatra Deni; Abdul Rasyid (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study aims to determine how the interpersonal communication patterns of teachers and deaf students and students' responses to communication symbols in SLB Taman Pendidikan Islam Medan. This research was conducted using descriptive qualitative research methods and data collection techniques used include interviews, observation and documentation. This research uses symbolic interaction theory which is a theory of how humans communicate with symbols that are carried in everyday life. The results of this study indicate that the interpersonal communication patterns of teachers and deaf students at SLB Taman Pendidikan Islam Medan are using lecture patterns, demonstration patterns and question and answer patterns. SLB Taman Pendidikan Islam Medan uses verbal (oral and written) and non-verbal (sign language) communication in the learning process. Students' responses to communication symbols are in the form of positive responses and negative responses. Positive responses are shown by looking for objects that are similar to the symbols given by the teacher. Negative responses are shown by emotional changes such as confusion, silence, and even rejection from students.